Analisis Mutu Organoleptik Ikan Tuna (Thunnus spp.) Di Kota Gorontalo Berdasarkan Rantai Distribusi - Lantu, Iin Susilawati; Sulistijowati, Rieny; Ibrahim, Pradipa Putra (Universitas Negeri Gorontalo, 2024)
The quality and distribution chain of tuna that is landed on the coast of Gorontalo from the fishermen's catch, the fish auction place (TPI) to the consumer is currently unknown, so there is a need for further information regarding the quality of the fish that is landed or that has been distributed which is of good quality. The aim of this research is to determine the organoleptic value of tuna (Thunnus spp.) based on the distribution chain, namely from fishermen's catches to fish auction sites (TPI) and fish retailers. The method used was tuna fish samples taken from three different places, namely fishermen, TPI and fish retailers, organoleptic tests and analyzed using Kruskal-wallis. Based on the results of the analysis of the fisherman sample, the highest score was 8, the TPI sample with a score of 7, and the lowest score was obtained for the PENGECER IKAN sample with a score of 6.43. Tuna fish samples from fishermen's catches and fish auction sites (TPI) meet the established standards for fresh fish raw materials, namely 7 (SNI 2013).